Prevalence and related factors of pregnant women received second hand smoke during pregnancy. - Ouiyanukoon , P.; Kalayasiri, R. (Chulalongkorn Medical Journal, 2023)
Background : Smoking is considered a social issue that affects both the smokers and the people around them. The smokers, making the surrounding people intake a fair amount of chemicals like the original smokers themselves; hence, they are given the named second-hand smokers. Objective : To examine the prevalence of pregnant women who are exposed to smoking and to study associated factors with second-hand smoking. Design : A cross-sectional descriptive study. Setting : King Chulalongkorn Memorial Hospital. Materials and Methods : Data are collected from pregnant women between 13 - 24 weeks gestation. Data from pregnant women at the Antenatal Care, Department of Obstetrics and Gynecology, King Chulalongkorn Memorial Hospital were collected by using demographic data questionnaire. Urinalysis assays were done by using direct barbituric acid (DBA) method. The data were analyzed using descriptive statistics, Chi - square and logistic regression analysis. Results : Of 296 pregnant women, the prevalence of pregnant women exposed to second-hand smoking during pregnancy is 39.19% (n = 116). Factors contributed to second-hand smoking were associated with young age, low income, low levels of education and having family members (spouse, father, mother and relatives) who are smoking. Exposure to smoking for 30 minutes or more and at the frequency of at least once a week are associated with second-hand smokers. Conclusion : The study has found that the prevalence of pregnant women who received second-hand smoke is 39.19 %. Factors associated with receiving second-hand smoke during pregnancy were age, income, levels of education, having family members, spouse, father, mother and relatives.